2013
DOI: 10.1177/1545968313496328
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gait and Balance in Patients With Leukoaraiosis Using Transcranial Direct Current Stimulation and Physical Training

Abstract: Combined anodal tDCS and PT improves gait and balance in this patient group, suggesting that tDCS could be an effective adjunct to PT in patients with leukoaraiosis, for whom no treatment is currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 26 publications
4
49
0
5
Order By: Relevance
“…The application of tDCS may, therefore, be useful to increase the activation of reticulospinal motoneurons or result in a stronger reticulospinal output, both of which could be beneficial for motor recovery and rehabilitation [6]. Interestingly, a recent study in patients with leukoaraoisis (hyperintensities in the subcortical white matter) showed that balance performance improved in response to a combined session of physical training and tDCS over the midline motor and premotor areas, but not following physical training alone [61]. In light of the present results, these improvements may have resulted from tDCS-induced reticulospinal facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The application of tDCS may, therefore, be useful to increase the activation of reticulospinal motoneurons or result in a stronger reticulospinal output, both of which could be beneficial for motor recovery and rehabilitation [6]. Interestingly, a recent study in patients with leukoaraoisis (hyperintensities in the subcortical white matter) showed that balance performance improved in response to a combined session of physical training and tDCS over the midline motor and premotor areas, but not following physical training alone [61]. In light of the present results, these improvements may have resulted from tDCS-induced reticulospinal facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that targeting neocortical regions involved with gait using noninvasive stimulation may be one therapeutic strategy to overcome the corticosubcortical disconnection caused by white matter lesions in leukoaraiosis [77].…”
Section: The Use Of Tdcs In Patients With Small Vessel Disease With Gmentioning
confidence: 94%
“…The principal result was that the combination of tDCS and locomotor training improves clinically relevant locomotor performance as measured by stride length ( = 0.047), stride length variability ( = 0.001), and gait velocity ( = 0.008; Figure 4(b)) in patients with leukoaraiosis [77]. We also observed improvements in the time taken to regain posture following a retropulsive stimulus in the tDCS and physical therapy group, but not with tDCS or physical therapy alone ( = 0.045; Figure 4(c)).…”
Section: The Use Of Tdcs In Patients With Small Vessel Disease With Gmentioning
confidence: 97%
“…LA patients may suffer from cognitive dysfunctions and depression as well as a variety of behavioral deficits, such as disturbed micturition and gait, balance disorders and even disability in daily life [3,4]. Sensorimotor disturbance is an early and the most pervasive symptom [5,6,7] and has become a research focus and a key issue for the clinical treatment of LA [8,9,10,11,12]. However, the relationship between the behavioral disturbances and certain cerebral changes in LA are unclear.…”
Section: Introductionmentioning
confidence: 99%